2019
DOI: 10.1002/jcp.29306
|View full text |Cite
|
Sign up to set email alerts
|

miR‐145 promotes miR‐133b expression through c‐myc and DNMT3A‐mediated methylation in ovarian cancer cells

Abstract: Ovarian cancer presents as malignant tumors in the female reproductive system with high mortality. MicroRNAs are involved in the progression of ovarian cancer; however, the regulatory relationship among miRs remains unclear. In our study, we verified that both miR-145 and miR-133b messenger RNA (mRNA) levels in ovarian cancer tissues were lower than in normal ovarian tissues, and their mRNA level in serum of patients with ovarian cancer was reduced. We demonstrated miR-145 targeted c-myc, and c-myc interacted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…Many recent studies have found that microRNA is closely related to ovarian cancer [27,28]. Previous studies confirmed that miR-145 regulated different biological functions of ovarian cancer by targeting different target genes [17][18][19][20]. However, the expression pattern and the m6A-regulated role of miR-145 in ovarian cancer were still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have found that microRNA is closely related to ovarian cancer [27,28]. Previous studies confirmed that miR-145 regulated different biological functions of ovarian cancer by targeting different target genes [17][18][19][20]. However, the expression pattern and the m6A-regulated role of miR-145 in ovarian cancer were still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the miR-145 agomir was able to repress WNT2B expression, and further led to an inhibition of the Wnt/β-catenin signaling in cervical cancer cells [45]. Another research also demonstrated that miR-145 could target c-myc which interacted physically with DNMT3A in ovarian cancer cells, and inhibit the Warburg effect through miR-133b/PKM2 pathways [46]. Similar to previous studies, our results revealed that tanshinone II A increased the expression of miR-145 at mRNA level on HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have found that microRNA is closely related to ovarian cancer [27,28]. Previous studies con rmed that miR-145 regulated different biological functions of ovarian cancer by targeting different target genes [17][18][19][20]. However, the expression pattern and the m6A-regulated role of miR-145 in ovarian cancer were still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-145 has different regulatory genes in different tumors; the molecular mechanisms of tumor suppressors are also different. Previous studies con rmed that miR-145 could regulate different biological functions of ovarian cancer by targeting different target genes [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%